Included and excluded: an intersectionality-based policy analysis of young migrants’ vulnerability to sexual violence in Sweden - Tanya Andersson Nystedt; Tobias Herder; Anette Agardh; Benedict Oppong Asamoah (International Journal for Equity in Health)
Abstract Introduction Young migrants are increasingly recognised as being particularly vulnerable to sexual violence. This vulnerability is largely structural, due to the different laws and policies impacting their access to rights and services. Post-structural approaches to policy argue that policies are not responses to existing problems, but rather that social issues are constructed through policy. They define both whether something is a problem and how that problem is to be addressed. The aim of this study was to understand how sexual violence is conceived of in the Swedish policy environment and how this interacts with the migration regime to affect young migrants’ vulnerability to sexual violence. Methods A systematic search was conducted to identify Swedish national-level policies: (1) addressing sexual violence; and (2) relating to the migration regime. 14 documents were included in the analysis: 6 addressed sexual violence, and 8 were related to migration. An intersectionality-based policy analysis was conducted by applying three questions to the relevant policies: (1) How is sexual violence conceived of in the policies? (2) How are young migrants represented in the policies? (3) How does the conception of sexual violence interact with the migration regime to impact young migrants’ vulnerability? Findings Power is central to how sexual violence is conceived of in Swedish policies, as is access to human right and services. Young persons and migrants are both identified as vulnerable groups in these policies but as separate categories. Structural sources of vulnerability are recognised but not addressed in policies addressing sexual violence. The migration regime works largely to restrict migrants’ access to rights and services, thereby contributing to young migrants’ vulnerability to sexual violence. Conclusion Although migrants and youth are included separately in policies addressing sexual violence, the migration regime largely works to exclude different groups of young migrants from access to rights and services and thereby increases their vulnerability to sexual violence.